Fiscal Policy Under Inflation Targeting - Øistein Røisland; Ragnar Torvik (Norges Bank, 2000)
The paper discusses the role of fiscal policy as an instrument for macroeconomic stabilisation when monetary policy pursues inflation targeting. Within a theoretical model of an open economy with a traded and non-traded sector, we show that inflation targeting may lead to large sectoral imbalances when fiscal policy is passive. There is a potentially large welfare gain from an active fiscal policy, in particular when sectoral stability is included in the welfare function. However, with reasonable parameter values, a small cost of adjusting fiscal policy reduces the optimal degree of activism considerably. The reason is that a given change in output requires a large change in the fiscal policy stance under inflation targeting, because of the monetary policy reaction function.
hdl:11250/2500390
Keywords: E52; E62; F41; 330; inflation targeting; fiscal policy; monetary policy; small open economy